Patani and the 15th Century Malay Ulama Network: A Historical Study of the Kitab Tarikh Fathani by Sheikh Faqih Ali al-Fathani - Syamsuri Ali (International Journal of Science and Society, 2023)
The purpose of this study was to find out about Patani and the 15th Century Malay Ulama Network. This study is based on library research using a historical approach. This is related to the variable Patani and the 15th-century Malay Ulama Network. The primary source of this study is the Kitab Tarih Fathani by Syeikh Faqih Ali al-Fathani, while other sources related to this variable, namely Patani and the Malay Ulama Network, are secondary sources. Based on the results of the research, it can be seen that Patani in the 15th century was the locus of the spread of Islam and developed with various aspects of its life, socio-political, socio-educational, socio-economic and socio-intellectualism, and had influence on other Islamic areas in Malay-Archipelago; and the Patani Ulama Network, mainly from the Bani Abbas genealogy, is one of the networks that contributed to the Islamization of the local Patani area (South Thailand) and the Malay-Archipelago region; and The contribution of the Ulama network of Bani Abbas Patani (South Thailand) to the Archipelago provides new insights into the development of the historical theory of Islamization in the Archipelago.